2020
DOI: 10.14300/mnnc.2020.15086
|View full text |Cite
|
Sign up to set email alerts
|

Influence of load on modeling and remodeling of bone tissue in experimental perimplantitis

Abstract: influence of load on modeling and remodeling of Bone Tissue in eXperimenTal perimplanTiTis sirak s. V. 1 , didenko m. o. 1 , sirak a. g. 1 , shchetinina e. e. 1 , sirak e. s. 2 , pogozheva a. V. 1 , petrosyan g. g. 1 , lenev V. n. 1 1 stavropol state medical university, russian federation 2 Kuban state medical university, Krasnodar, russian federation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Our findings indicated that in groups 1 and 2 there was no negative effect of delayed functional load on the stability of dental implants, which is consistent with both the experimental data and the clinical observations for implantation systems [10,11].…”
Section: стоматологияsupporting
confidence: 90%
“…Our findings indicated that in groups 1 and 2 there was no negative effect of delayed functional load on the stability of dental implants, which is consistent with both the experimental data and the clinical observations for implantation systems [10,11].…”
Section: стоматологияsupporting
confidence: 90%